Solid-state battery cell and method of manufacturing the same, battery device, and power using device

CN123018055APending Publication Date: 2026-10-30CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510558699.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

负极采用硅基材料的固态电池单体可以具有更高的能量密度,但是,硅基材料在循环过程中不断膨胀收缩,这种膨胀收缩容易导致接触失效,并引发固态电池单体容量快速衰减

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018055A_ABST
    Figure CN123018055A_ABST
Patent Text Reader

Abstract

The present disclosure provides a solid-state battery monomer, a preparation method thereof, a battery device and a power utilization device. The solid-state battery monomer comprises a negative electrode layer, an electrolyte layer and a positive electrode layer, the electrolyte layer is located between the negative electrode layer and the positive electrode layer, the negative electrode layer comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer comprises a silicon-based material and a negative electrode conductive agent, the average particle size of the silicon-based material is 15 nm-200 nm, the NP ratio of the solid-state battery monomer is greater than 0 and less than 1, and the NP ratio is the ratio of the negative electrode unit area capacity to the positive electrode unit area capacity. The solid-state battery monomer has high energy density, and at the same time has high initial coulomb efficiency, good cycle stability and good kinetic performance under low external pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a solid-state battery cell and its preparation method, battery device, and power consumption device. Background Technology

[0002] Compared to battery cells using liquid electrolytes, solid-state battery cells use solid electrolyte materials, making them less prone to combustion and explosion, and offering high reliability and high energy density. Solid-state battery cells using silicon-based materials for the negative electrode can achieve even higher energy density; however, silicon-based materials continuously expand and contract during cycling, which can easily lead to contact failure and cause rapid capacity decay in solid-state battery cells. Summary of the Invention

[0003] This disclosure provides a solid-state battery cell and its preparation method, battery device and power supply device. The solid-state battery cell has high energy density, high initial coulombic efficiency under low external pressure, good cycle stability and good kinetic performance.

[0004] In a first aspect, this disclosure provides a solid-state battery cell, including a negative electrode layer, an electrolyte layer, and a positive electrode layer. The electrolyte layer is located between the negative electrode layer and the positive electrode layer. The negative electrode layer includes a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector. The negative electrode active material layer includes a silicon-based material and a negative electrode conductive agent. The average particle size of the silicon-based material is 15nm-200nm. The NP ratio of the solid-state battery cell is greater than 0 and less than 1. The NP ratio is the ratio of the unit area capacity of the negative electrode to the unit area capacity of the positive electrode.

[0005] The solid-state battery cell disclosed herein has an NP ratio greater than 0 and less than 1, and the average particle size of the silicon-based material is 15nm-200nm. By making the negative electrode's unit area capacity smaller than that of the positive electrode and by making the silicon-based material have a smaller particle size, when the solid-state battery cell operates under low external pressure, in addition to some lithium undergoing an alloying lithium intercalation reaction with the silicon-based material, excess lithium will accumulate between the silicon-based material particles and deposit through the negative electrode active material layer on the surface of the negative electrode current collector, i.e., deposited between the negative electrode active material layer and the negative electrode current collector. These lithium particles that accumulate between the silicon-based material particles can serve as lithium-ion transport channels, improving the lithium-ion transport performance and kinetic performance of the negative electrode. The lithium deposited through the negative electrode active material layer between the negative electrode active material layer and the negative electrode current collector can also promote the change from the alloying lithium intercalation reaction mechanism to the lithium metal deposition / stripping mechanism as the main mechanism during subsequent charge-discharge cycles of the solid-state battery cell. At the same time, the negative electrode active material layer can act as a barrier layer, reducing the risk of short circuit between lithium metal and the positive electrode. This can improve the initial coulombic efficiency, cycle stability, and kinetic performance of the solid-state battery cell.

[0006] The average particle size of the silicon-based material in the negative electrode active material layer disclosed herein is 15nm-200nm. The small average particle size of the silicon-based material results in small volume expansion of the negative electrode. Furthermore, the small average particle size of the silicon-based material leads to better kinetic performance, which is beneficial for improving the cycle stability and kinetic performance of solid-state battery cells.

[0007] The average particle size of the silicon-based material in the negative electrode active material layer disclosed herein is 15nm-200nm. The silicon-based material has a small average particle size and high surface activity, which results in the silicon-based material particles usually having a silicon oxide layer on their surface, resulting in poor electronic conductivity. By including a negative electrode conductive agent in the negative electrode active material layer, the electronic conductivity of the negative electrode can be improved, thereby improving the kinetic performance of the solid-state battery cell.

[0008] Therefore, the solid-state battery cell disclosed herein has high energy density, high initial coulombic efficiency, good cycle stability and good kinetic performance under low external pressure.

[0009] In some embodiments, the average particle size of the silicon-based material is 30 nm to 85 nm.

[0010] In some embodiments, the volumetric particle size Dv50 of the silicon-based material is 15nm-200nm.

[0011] In some embodiments, the NP ratio of a solid-state battery cell is 0.05-0.3.

[0012] When the NP ratio of a solid-state battery cell is within the above range, the thickness uniformity of the negative electrode active material layer is good, and lithium is more likely to accumulate between silicon-based material particles, thus serving as a better lithium-ion transport channel. Lithium can also easily pass through the negative electrode active material layer and deposit between the negative electrode active material layer and the negative electrode current collector, which is more conducive to the stable cycling of the solid-state battery cell under low external pressure. In addition, the solid-state battery cell also has high initial coulombic efficiency and high cycle capacity retention.

[0013] In some embodiments, the solid-state battery cell operates under an external pressure of less than 10 MPa.

[0014] In some embodiments, silicon-based materials include pure silicon or silicon-containing materials.

[0015] In some embodiments, the silicon-containing material includes metal-doped silicon, wherein the mass fraction of Si element in the metal-doped silicon is greater than or equal to 75% and less than 100%. A small amount of doped metal element can reduce the volume expansion of silicon and improve its electronic conductivity without affecting its high specific capacity, thereby improving the cycle stability and kinetic performance of solid-state battery cells.

[0016] In some embodiments, the atomic radius r of the dopant metal element in metal-doped silicon is the same as the atomic radius r of the Si element. si Satisfy (rr) si ) / r×100% is between 0 and 25%.

[0017] In some embodiments, the doping metal element in metal-doped silicon includes one or more of Ge, Sn, Fe, Ni, Al, and Cu.

[0018] In some embodiments, based on the total mass of the negative electrode active material layer (100%), the mass fraction of Si in the negative electrode active material layer is greater than 50% and less than 100%, optionally between 80% and 98%. When the mass fraction of Si in the negative electrode active material layer is less than 50%, the capacity provided by the silicon-based material is low, which is detrimental to obtaining high-energy-density solid-state battery cells. When the mass fraction of Si in the negative electrode active material layer is high, the capacity provided by the silicon-based material is greater, but the negative electrode volume expansion is large, and the negative electrode interface is prone to contact failure when the solid-state battery cell operates under low external pressure. This disclosure, by setting the average particle size of the silicon-based material to 15nm-200nm, can reduce the negative electrode volume expansion and stabilize the negative electrode interface, thereby enabling the solid-state battery cell to achieve high energy density while exhibiting high initial coulombic efficiency, good cycle stability, and good kinetic performance under low external pressure.

[0019] In some embodiments, the negative electrode conductive agent includes a linear conductive agent. By including a linear conductive agent in the negative electrode conductive agent, it is beneficial to form a better electronic conductive network in the negative electrode active material layer, thereby improving the electronic conductivity of the negative electrode. This can promote the rapid transfer of lithium between silicon-based material particles, facilitate the rapid passage of lithium through the negative electrode active material layer and its deposition between the negative electrode active material layer and the negative electrode current collector, and improve the dynamic performance of the solid-state battery cell.

[0020] In some embodiments, the linear conductive agent includes one or more of carbon nanotubes, carbon nanofibers, and vapor-grown carbon fibers.

[0021] In some embodiments, the linear conductive agent accounts for 0.5%-2% of the mass of the negative electrode active material layer.

[0022] In some embodiments, the negative electrode conductive agent further includes a dot-shaped conductive agent and / or a surface-shaped conductive agent.

[0023] In some embodiments, the negative electrode active material layer further includes a solid electrolyte material, which includes one or more of sulfide solid electrolyte materials, halide solid electrolyte materials, oxide solid electrolyte materials, and polymer solid electrolyte materials.

[0024] In some embodiments, the porosity of the negative electrode active material layer is 10%-20%. When the porosity of the negative electrode active material layer is within this range, the silicon-based material exhibits good electronic contact, which is beneficial for improving the lithium-ion transport performance of the negative electrode and enhancing the cycle stability and kinetic performance of the solid-state battery cell.

[0025] In some embodiments, the thickness of the negative electrode active material layer is 1 μm-40 μm.

[0026] In some embodiments, the thickness of the negative electrode active material layer is 2μm-6μm.

[0027] In some embodiments, the negative electrode layer further includes a metal layer located between the negative electrode current collector and the negative electrode active material layer. The metal layer includes a metal element capable of forming an alloy or solid solution with lithium. The inclusion of a metal element capable of forming an alloy or solid solution with lithium in the metal layer can reduce the lithium nucleation overpotential, improve the uniformity of lithium deposition, and enhance the cycle performance of the solid-state battery cell.

[0028] Optionally, the metal element in the metal layer includes one or more of Au, Ag, Mg, Zn, Sn, Bi, In, and Al.

[0029] Optionally, the thickness of the metal layer is 1nm-50nm.

[0030] In some embodiments, the negative electrode layer further includes a lithium-based metal layer located between the negative electrode current collector and the negative electrode active material layer. Before charging the solid-state battery cell of this disclosure, the presence of a lithium-based metal layer between the negative electrode current collector and the negative electrode active material layer can compensate for irreversible lithium loss from the negative electrode active material layer, thereby further improving the initial coulombic efficiency and capacity retention of the solid-state battery cell.

[0031] Optionally, the lithium-based metal layer includes lithium or a lithium alloy.

[0032] Optionally, the thickness of the lithium-based metal layer is 0.5 μm-50 μm.

[0033] In some embodiments, the positive electrode layer includes a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector. The positive electrode active material layer includes a solid electrolyte material and a positive electrode active material. The positive electrode active material includes one or more of lithium transition metal oxides and their modified materials, lithium phosphates and their modified materials, lithium titanate, lithium niobate, sulfur, selenium, and tellurium. The solid electrolyte material includes one or more of sulfide solid electrolyte materials, halide solid electrolyte materials, oxide solid electrolyte materials, and polymer solid electrolyte materials.

[0034] In some embodiments, the electrolyte layer includes one or more of sulfide solid electrolyte materials, halide solid electrolyte materials, oxide solid electrolyte materials, and polymer solid electrolyte materials.

[0035] In some embodiments, the positive electrode capacity per unit area is 2.5 mAh / cm². 2 -6mAh / cm 2 .

[0036] Secondly, this disclosure provides a method for preparing a solid-state battery cell, comprising the following steps: providing a negative electrode layer, an electrolyte layer, and a positive electrode layer; assembling the negative electrode layer, electrolyte layer, and positive electrode layer; and pressing them to obtain a solid-state battery cell. The electrolyte layer is located between the negative electrode layer and the positive electrode layer. The negative electrode layer includes a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector. The negative electrode active material layer includes a silicon-based material and a negative electrode conductive agent. The average particle size of the silicon-based material is 15nm-200nm. The NP ratio of the solid-state battery cell is greater than 0 and less than 1. The NP ratio is the ratio of the negative electrode unit area capacity to the positive electrode unit area capacity.

[0037] Thirdly, this disclosure provides a battery device comprising a plurality of solid-state battery cells according to the first aspect or solid-state battery cells prepared by the preparation method of the second aspect.

[0038] Fourthly, this disclosure provides an electrical device that includes a solid-state battery cell (as described in the first aspect) or a battery device (as described in the third aspect). Attached Figure Description

[0039] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings used in the embodiments of this disclosure will be briefly described below. Obviously, the drawings described below are merely some embodiments of this disclosure. For those skilled in the art, other drawings can be obtained based on the drawings without any creative effort.

[0040] Figure 1 A schematic diagram of a solid-state battery cell provided in some embodiments of this disclosure is shown.

[0041] Figure 2 A schematic diagram of an electrical device provided in some embodiments of this disclosure is shown.

[0042] The accompanying drawings are not necessarily drawn to scale. Detailed Implementation

[0043] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the solid-state battery cell, its preparation method, battery device, and power-consuming device of this disclosure. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this disclosure and are not intended to limit the subject matter of the claims.

[0044] The "range" disclosed in this disclosure is defined by a lower limit and an upper limit, whereby a given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also expected. Furthermore, if minimum range values ​​1 and 2 are listed, and if maximum range values ​​3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this disclosure, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0045] Unless otherwise specified, all embodiments and optional embodiments of this disclosure may be combined with each other to form new technical solutions, and such technical solutions should be considered as included in the disclosure of this disclosure.

[0046] Unless otherwise specified, all technical features and optional technical features of this disclosure can be combined to form new technical solutions, and such technical solutions should be considered as included in the disclosure of this disclosure.

[0047] Unless otherwise specified, all steps in this disclosure may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0048] Unless otherwise specified, in this disclosure, the terms "first," "second," etc., are used to distinguish different objects, rather than to describe a specific order or primary / secondary relationship.

[0049] In this disclosure, the terms "multiple" or "a variety" refer to two or more kinds.

[0050] In the description of the embodiments of this disclosure, unless otherwise specified, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0051] Unless otherwise stated, the test temperature for all parameters mentioned in this disclosure is 25°C.

[0052] The solid-state battery cells mentioned in the embodiments of this disclosure can independently perform charging and discharging functions. Solid-state battery cells can be cylindrical, cuboid, or other shapes, etc., and the embodiments of this disclosure are not limited in this respect. Figure 1 This is an example of a rectangular solid-state battery cell 5.

[0053] The battery apparatus mentioned in the embodiments of this disclosure may include one or more battery cell assemblies for providing voltage and capacity. The battery cell assembly may include multiple solid-state battery cells, which are connected in series, parallel, or mixed connections via busbars.

[0054] In some embodiments, a battery cell assembly is typically formed by arranging multiple solid-state battery cells.

[0055] As an example, a battery cell assembly can be a battery module, which is formed by arranging and fixing multiple solid-state battery cells together to form an independent module. As another example, a battery module can be formed by bundling multiple solid-state battery cells together with cable ties.

[0056] In some embodiments, the battery device may be a battery pack, which includes a housing and one or more individual battery cells housed within the housing.

[0057] As an example, the battery cell assembly can be a battery module, which can be housed in a housing by fixing the battery module in the housing.

[0058] As an example, battery cell assemblies can also be housed in a housing by directly fixing multiple solid-state battery cells to the housing.

[0059] As an example, the enclosure may include a first enclosure and a second enclosure. The first enclosure and the second enclosure are fastened together to form a closed space inside the enclosure to house the individual battery cells. Here, "closed" refers to covering or closing, and can be either sealed or unsealed. The first enclosure may be a top cover or a bottom plate.

[0060] As an example, the enclosure may include a top cover, a frame, and a bottom plate. The top cover and bottom plate are connected to the frame, creating an enclosed space inside the enclosure to house the individual battery cells.

[0061] In some embodiments, the housing may be part of the vehicle's chassis structure. For example, a portion of the housing may be at least a part of the vehicle's floor, or a portion of the housing may be at least a part of the vehicle's crossbeams and longitudinal beams.

[0062] The technical solutions described in this disclosure are applicable to various electrical devices that use solid-state battery cells or battery devices, such as, but not limited to, mobile devices (e.g., mobile phones, tablets, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc. Solid-state battery cells and battery devices are used to store or provide electrical energy.

[0063] Figure 2 This is a schematic diagram of an example electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc.

[0064] The solid-state battery cells disclosed herein may include coin cells, molded cells, hard-case cells, pouch cells, etc.

[0065] Silicon-based materials can provide high specific capacity, which is beneficial for achieving high energy density in solid-state battery cells. However, silicon-based materials continuously expand and contract during cycling, and this expansion and contraction can easily lead to interfacial contact failure. Therefore, solid-state battery cells using silicon-based materials as the negative electrode usually require a large external pressure during charge-discharge cycles to maintain effective interfacial contact between materials. However, high cycle pressure increases the weight of the entire battery device and sacrifices energy density; while low cycle pressure, such as external pressure below 10 MPa, usually leads to insufficient interfacial contact and rapid capacity decay, and the lower the cycle pressure, the faster the capacity decay, thus limiting the practical application of solid-state battery cells.

[0066] In view of this, embodiments of the present disclosure provide a solid-state battery cell that has high energy density, high initial coulombic efficiency, good cycle stability and good kinetic performance under low external pressure.

[0067] The solid-state battery cell provided in this embodiment includes a negative electrode layer, an electrolyte layer, and a positive electrode layer, with the electrolyte layer located between the negative electrode layer and the positive electrode layer.

[0068] The negative electrode layer includes a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector. The negative electrode active material layer includes a silicon-based material and a negative electrode conductive agent. The average particle size of the silicon-based material is 15nm-200nm.

[0069] The negative electrode current collector has two surfaces opposite each other in its thickness direction, and the negative electrode active material layer is disposed on one or both of the two opposite surfaces of the negative electrode current collector.

[0070] The NP ratio of a solid-state battery cell is greater than 0 and less than 1. The NP ratio (Negative / Positive Ratio) is the ratio of the negative electrode capacity per unit area to the positive electrode capacity per unit area, i.e., negative electrode capacity per unit area / positive electrode capacity per unit area.

[0071] The NP ratio can be tested using the following method.

[0072] The negative electrode layer was removed from a solid-state battery cell and placed in a solid-state battery mold for testing. The counter electrode was a lithium-indium alloy sheet separated by an electrolyte layer. The battery was discharged to 0.01V (vs. Li) at a current density of 0.1C. + / Li), and then charged to 2V at a current density of 0.1C (vs. Li). + The resulting charging capacity ( / Li) is the negative electrode capacity. Negative electrode capacity per unit area = negative electrode capacity / negative electrode layer area.

[0073] The positive electrode layer is removed from a solid-state battery cell and placed in a solid-state battery mold for testing. A lithium-indium alloy sheet is used as the counter electrode, separated by an electrolyte layer. The battery is charged at a current density of 0.1C to the upper cutoff voltage, and then discharged at a current density of 0.1C to the lower cutoff voltage. The resulting discharge capacity is the positive electrode capacity. Positive electrode capacity per unit area = Positive electrode capacity / Positive electrode layer area.

[0074] The NP ratio of a solid-state battery cell = negative electrode unit area capacity / positive electrode unit area capacity.

[0075] Both the upper and lower cutoff voltages are known in the art, and the voltages recommended in the product specifications can be used. For example, the positive electrode active material is a lithium transition metal oxide or its modified form, such as LiNi. 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (abbreviated as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (abbreviated as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (abbreviated as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (abbreviated as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (abbreviated as NCM811), LiNi 0.96 Co 0.02 Mn 0.02 O2 (abbreviated as Ni96), LiNi 0.80 Co 0.15 Al 0.05 O2, the upper limit cutoff voltage can be 4.3V (vs. Li). + / Li), the lower cutoff voltage can be 2V (vs.Li). + / Li).

[0076] Currently, solid-state battery cells using silicon anodes are designed with an NP ratio greater than or equal to 1, and these cells are typically charged and discharged under high external pressure to minimize the risk of lithium ion deposition and dendrite formation on the anode surface due to insufficient anode capacity. However, when these solid-state battery cells operate under low external pressure, such as below 10 MPa, the capacity rapidly decreases due to insufficient contact at the silicon-based anode interface. Simultaneously, lithium ions are more likely to deposit and form lithium dendrites on the anode surface, increasing the risk of short circuits between the positive and negative electrodes.

[0077] The solid-state battery cell disclosed herein has an NP ratio greater than 0 and less than 1, and the average particle size of the silicon-based material is 15nm-200nm. By making the negative electrode's unit area capacity smaller than that of the positive electrode and by making the silicon-based material have a smaller particle size, when the solid-state battery cell operates under low external pressure, in addition to some lithium undergoing an alloying lithium intercalation reaction with the silicon-based material, excess lithium will accumulate between the silicon-based material particles and deposit through the negative electrode active material layer on the surface of the negative electrode current collector, i.e., deposited between the negative electrode active material layer and the negative electrode current collector. These lithium particles that accumulate between the silicon-based material particles can serve as lithium-ion transport channels, improving the lithium-ion transport performance and kinetic performance of the negative electrode. The lithium deposited through the negative electrode active material layer between the negative electrode active material layer and the negative electrode current collector can also promote the change from the alloying lithium intercalation reaction mechanism to the lithium metal deposition / stripping mechanism as the main mechanism during subsequent charge-discharge cycles of the solid-state battery cell. At the same time, the negative electrode active material layer can act as a barrier layer, reducing the risk of short circuit between lithium metal and the positive electrode. This can improve the initial coulombic efficiency, cycle stability, and kinetic performance of the solid-state battery cell.

[0078] Silicon-based materials, such as pure silicon, typically have low electronic conductivity, and the higher their average particle size, the more severe the anode volume expansion. When solid-state battery cells operate under low external pressure, the anode interface is prone to contact failure. At the same time, solid-state battery cells have high irreversible lithium loss, resulting in low initial coulombic efficiency and capacity retention.

[0079] The average particle size of the silicon-based material in the negative electrode active material layer disclosed herein is 15nm-200nm. The small average particle size of the silicon-based material results in small volume expansion of the negative electrode. Furthermore, the small average particle size of the silicon-based material leads to better kinetic performance, which is beneficial for improving the cycle stability and kinetic performance of solid-state battery cells.

[0080] The average particle size of the silicon-based material in the negative electrode active material layer disclosed herein is 15nm-200nm. The silicon-based material has a small average particle size and high surface activity, which results in the silicon-based material particles usually having a silicon oxide layer on their surface, resulting in poor electronic conductivity. By including a negative electrode conductive agent in the negative electrode active material layer, the electronic conductivity of the negative electrode can be improved, thereby improving the kinetic performance of the solid-state battery cell.

[0081] Therefore, the solid-state battery cell disclosed herein has high energy density, high initial coulombic efficiency, good cycle stability and good kinetic performance under low external pressure.

[0082] The solid-state battery cell disclosed herein can operate under external pressures below 10 MPa. That is, the solid-state battery cell disclosed herein exhibits high initial coulombic efficiency, good cycle stability, and good kinetic performance under external pressures below 10 MPa.

[0083] Optionally, the solid-state battery cell of this disclosure can operate under an external pressure below 5 MPa. That is, the solid-state battery cell of this disclosure exhibits high initial coulombic efficiency, good cycle stability, and good kinetic performance under an external pressure below 5 MPa.

[0084] The NP ratio of a solid-state battery cell is greater than 0 and less than 1, for example, it can be 0.9, 0.86, 0.84, 0.82, 0.8, 0.78, 0.76, 0.74, 0.72, 0.7, 0.68, 0.66, 0.64, 0.62, 0.6, 0.58, 0.56, 0.54, 0.52, 0.5, 0.48, 0.46, 0.44, 0.42, 0.4, 0.38, 0.36 0.34, 0.32, 0.3, 0.29, 0.28, 0.27, 0.26, 0.25, 0.24, 0.23, 0.22, 0.21, 0.2, 0.19, 0.18, 0.17, 0.16, 0.15, 0.14, 0.13, 0.12, 0.11, 0.1, 0.09, 0.08, 0.07, 0.06, 0.05, or any range of the above values.

[0085] Optionally, the NP ratio of a single solid-state battery cell can be 0.05-0.9, 0.05-0.8, 0.05-0.7, 0.05-0.6, 0.05-0.5, 0.05-0.48, 0.05-0.46, 0.05-0.44, 0.05-0.42, 0.05-0.4, 0.05-0.38, or 0.05-0.3. 6, 0.05-0.34, 0.05-0.32, 0.05-0.3, 0.05-0.28, 0.05-0.26, 0.05-0.24, 0.05-0.22, 0.05-0.2, 0.05-0.18, 0.05-0.16, 0.05-0.14, 0.05-0.12, 0.05-0.1.

[0086] When the NP ratio of a solid-state battery cell is within the above range, the thickness uniformity of the negative electrode active material layer is good, and lithium is more likely to accumulate between silicon-based material particles, thus serving as a better lithium-ion transport channel. Lithium can also easily pass through the negative electrode active material layer and deposit between the negative electrode active material layer and the negative electrode current collector, which is more conducive to the stable cycling of the solid-state battery cell under low external pressure. In addition, the solid-state battery cell also has high initial coulombic efficiency and high cycle capacity retention.

[0087] The average particle size of silicon-based materials is 15nm-200nm, for example, it can be 15nm, 20nm, 22nm, 24nm, 26nm, 28nm, 30nm, 32nm, 34nm, 36nm, 38nm, 40nm, 42nm, 44nm, 46nm, 48nm, 50nm, 52nm, 54nm, 56nm, 58nm, 60nm, 62nm, 64nm, 66nm, 68nm, 70nm, 72nm, 74nm, 76nm, 78nm, 80nm, 85nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, or any combination of the above values.

[0088] Optionally, the average particle size of the silicon-based material is 30nm-200nm, 30nm-150nm, 30nm-100nm, 30nm-85nm, 30nm-75nm, 30nm-60nm, or 30nm-50nm.

[0089] The average particle size of silicon-based materials can be tested as follows: Using a scanning electron microscope (SEM) according to JY / T010-1996, obtain an SEM image of the negative electrode layer. Randomly select a test sample with dimensions of 50mm x 100mm on the negative electrode layer. Randomly select multiple test areas (e.g., 5) within the test sample, and read the particle size of each silicon-based material particle in each test area at a certain magnification (e.g., 500x or higher). Count the number and particle size of silicon-based material particles in each test area, and take the arithmetic mean of the particle sizes of all silicon-based material particles in each test area as the average particle size of the silicon-based material. To ensure the accuracy of the test results, multiple test samples (e.g., 10) can be used for the above test, and the average value of each test sample can be taken as the final test result. The testing instrument can be a ZEISS Sigma 300. It should be noted that when the particles are irregularly shaped, the distance between the two farthest points on the particle is taken as the particle size.

[0090] In some embodiments, the volumetric particle size Dv50 of the silicon-based material is 15nm-200nm, for example, it can be 15nm, 20nm, 22nm, 24nm, 26nm, 28nm, 30nm, 32nm, 34nm, 36nm, 38nm, 40nm, 42nm, 44nm, 46nm, 48nm, 50nm, 52nm, 54nm, 56nm, 58nm, 60nm, 62nm, 64nm, 66nm, 68nm, 70nm, 72nm, 74nm, 76nm, 78nm, 80nm, 85nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, or any range of the above values.

[0091] Dv50 represents the particle size corresponding to a cumulative volumetric distribution percentage of 50% for the material. It can be measured using a laser particle size analyzer, referring to GB / T19077-2016. During testing, add 1g of the powder sample to a clean small beaker, add 20ml of deionized water, and sonicate at 53kHz / 120W for 5 minutes to ensure complete dispersion. Turn on the laser particle size analyzer, clean the optical path system, and automatically test the background. Stir the sonicated solution to ensure uniform dispersion, place it in the sample cell as required, and begin measuring the particle size. A MasterSizer 3000 laser particle size analyzer can be used as the testing instrument.

[0092] Silicon-based materials exist in the form of particles within the negative electrode active material layer. In some embodiments, the morphology of the silicon-based materials includes spherical and / or near-spherical shapes.

[0093] In some embodiments, silicon-based materials include pure silicon or silicon-containing materials.

[0094] In some embodiments, the silicon-containing material includes metal-doped silicon.

[0095] Optionally, the mass fraction of Si in the metal-doped silicon is greater than or equal to 75% and less than 100%.

[0096] Doping with a small amount of metal elements can reduce the volume expansion of silicon and improve its electronic conductivity without affecting its high specific capacity, thereby improving the cycle stability and kinetic performance of solid-state battery cells.

[0097] Optionally, the atomic radius r of the dopant metal element in the metal-doped silicon is the same as the atomic radius r of the Si element. si Satisfy (rr) si (r) / r×100% is between 0 and 25%. Alternatively, (rr) si) / r×100% is between 0 and 15%, and between 0 and 10%.

[0098] Optionally, the doping metal element in metal-doped silicon may include one or more of Ge, Sn, Fe, Ni, Al, and Cu.

[0099] The atomic radii of Si and doped metal elements can be obtained from Lange's handbook of chemistry.

[0100] In some embodiments, with the total mass of the negative electrode active material layer as 100%, the mass fraction of Si element in the negative electrode active material layer can be greater than 50% and less than 100%, for example, it can be 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, or any range of the above values.

[0101] The mass fraction of Si in the negative electrode active material layer is less than 50%, and the capacity that silicon-based materials can provide is small, which is not conducive to obtaining high energy density solid-state battery cells.

[0102] The high mass fraction of Si in the negative electrode active material layer allows for greater capacity from silicon-based materials, but also results in significant negative electrode volume expansion. This makes the negative electrode interface prone to contact failure when the solid-state battery cell operates under low external pressure. This disclosure addresses this issue by using a silicon-based material with an average particle size of 15nm-200nm, which reduces negative electrode volume expansion and stabilizes the negative electrode interface. This allows the solid-state battery cell to achieve high energy density while maintaining high initial coulombic efficiency, good cycle stability, and excellent kinetic performance under low external pressure.

[0103] Optionally, based on the total mass of the negative electrode active material layer as 100%, the mass fraction of Si element in the negative electrode active material layer can be 55%-98%, 60%-98%, 65%-98%, 70%-98%, 75%-98%, 80%-98%, 82%-98%, 84%-98%, 86%-98%, 88%-98%, or 90%-98%.

[0104] The mass fraction of Si in the negative electrode active material layer can be measured using an inductively coupled plasma optical emission spectrometer (ICP). The testing standard can be found in JY / T 015 1996.

[0105] The negative electrode active material layer includes a negative electrode conductive agent. The negative electrode conductive agent is a carbon-based conductive agent.

[0106] In some embodiments, the negative electrode conductive agent includes a linear conductive agent.

[0107] The silicon-based material in the negative electrode active material layer of this disclosure has an average particle size of 15nm-200nm. The small average particle size of the silicon-based material results in high surface activity, which typically leads to a silicon oxide layer on the surface of the silicon-based material particles, resulting in poor electronic conductivity. By including a linear conductive agent in the negative electrode conductive agent, it is beneficial to form a better electronic conductivity network in the negative electrode active material layer, thereby improving the electronic conductivity of the negative electrode. This promotes rapid lithium transfer between silicon-based material particles, facilitates rapid lithium penetration through the negative electrode active material layer and deposition between the negative electrode active material layer and the negative electrode current collector, and improves the kinetic performance of the solid-state battery cell.

[0108] Optionally, the linear conductive agent may include one or more of carbon nanotubes (CNTs), carbon nanofibers, and vapor-grown carbon fibers (VGCF).

[0109] Alternatively, the linear conductive agent may include carbon nanotubes (CNTs).

[0110] Carbon nanotubes (CNTs) have good electronic conductivity, which is conducive to the formation of a better electronic conductivity network in the negative electrode active material layer, thereby improving the electronic conductivity of the negative electrode. They are also conducive to reducing the mass ratio of the negative electrode conductive agent in the negative electrode active material, increasing the mass ratio of the negative electrode active material, and improving the energy density of the solid-state battery cell.

[0111] Optionally, the linear conductive agent accounts for 0.5%-2% of the mass of the negative electrode active material layer.

[0112] In some embodiments, the negative electrode conductive agent may further include dot-shaped conductive agents and / or surface-shaped conductive agents.

[0113] Alternatively, the planar conductive agent may include graphene.

[0114] Optionally, the spherical conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, and carbon dots.

[0115] In some embodiments, the negative electrode active material layer further includes a negative electrode binder.

[0116] Optionally, the negative electrode binder may include, but is not limited to, one or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, polyacrylic acid, polymethacrylic acid, sodium polyacrylate, polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS), methyl vinyl silicone rubber, nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), thermoplastic styrene-butadiene rubber (SBS), isoprene rubber, butadiene rubber (BR), ethyl cellulose, fluororubber, and acrylate rubber.

[0117] In some embodiments, the negative electrode active material layer may further include a solid electrolyte material.

[0118] Optionally, the solid electrolyte material in the negative electrode active material layer may include one or more of the following: sulfide solid electrolyte material, halide solid electrolyte material, oxide solid electrolyte material, and polymer solid electrolyte material.

[0119] In some embodiments, the sulfide solid electrolyte material may include, but is not limited to, one or more of the following: silver-germanium sulfide type, LGPS type, lithium sulfide-phosphorus pentasulfide complex type sulfide solid electrolyte materials.

[0120] Optionally, the sulfide solid electrolyte material of the silver-germanium sulfide type may include Li 6±s P 1-j A j S 5±s- t B t X 1±s The material has the following properties: 0≤j<1, 0≤t<1, 0≤s<1, A includes one or more elements from Ge, Si, Sn and Sb, B includes one or more elements from O, Se and Te, and X includes one or more elements from Cl, Br, I and F.

[0121] Optionally, LGPS-type sulfide solid electrolyte materials may include those with the chemical formula Li 10±δ5 Ge 1-g G g P 2-q Q q S 12- w W w The material has the following properties: 0≤δ5<1, 0≤g≤1, 0≤q≤2, 0≤w<1, G includes one or two elements from Si and Sn, Q includes Sb, and W includes one or more elements from O, Se, Te, Cl, Br, I, and F.

[0122] Alternatively, the lithium sulfide-phosphorus pentasulfide complex type sulfide solid electrolyte material may include a chemical formula of (100-u-v)Li2S·uP2S5·vM m N n wherein 0<u<100, 0≤v<100, 0≤u+v<100, 0≤m<4, 0≤n<6, M includes one or more elements selected from Li, B, Ge, Si, Sn and Sb, and N includes one or more elements selected from S, Se, Te, O, Cl, Br, I and F.

[0123] As an example, the sulfide solid electrolyte material may include, but is not limited to, one or more of Li6PS5Cl, Li6PS5Br, Li 10 GeP2S 12 , Li3PS4, Li7P3S 11 .

[0124] In some embodiments, the halide solid electrolyte material may include, but is not limited to, one or more of Li3YCl6, Li3YBr6, Li3ErCl6, Li3InCl6, and Li3InBr6.

[0125] In some embodiments, the oxide solid electrolyte material may include one or more of a NASICON-type solid electrolyte, a LISICON-type solid electrolyte, a perovskite-type solid electrolyte, and a garnet-type solid electrolyte.

[0126] As an example, the oxide solid electrolyte material may include, but is not limited to, Li5La3Ti2O 12 , Li7La3Zr2O 12 , Li4Ti5O 12 , Li 14 Zn(GeO4)4, LiTi2(PO4)3, Li 1+x Al x Ti 2-x (PO4)3, Li 1+y Al y Ge 2-y (PO4)3, where 0<x<2 and 0<y<2.

[0127] In some embodiments, the polymer solid electrolyte material may be formed by complexing a polymer matrix material with a lithium salt. Optionally, the polymer matrix material may be one or more of, but not limited to, polyethylene oxide (PEO) and its derivatives, polypropylene oxide (PPO) and its derivatives, polycarbonate (PPC), polyacrylonitrile (PAN), polysiloxane (PDMS), polyvinylidene fluoride (PVDF), and polymethyl methacrylate (PMMA). Optionally, the lithium salt may be one or more of, but not limited to, LiClO4, LiAsF4, LiPF6, LiBF4, LiTFSI, and LiFSI.

[0128] Optionally, the polymer solid electrolyte material may also include an inert filler, which can reduce the crystallinity of the polymer and improve its mechanical properties. Optionally, the inert filler may be one or more of TiO2, Al2O3, ZrO2, and SiO2.

[0129] Optionally, the mass fraction of the solid electrolyte material in the negative electrode active material layer can be greater than 0 and less than or equal to 15%.

[0130] In some embodiments, the porosity of the negative electrode active material layer can be 10%-20%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or any range of the above values.

[0131] When the porosity of the negative electrode active material layer is within the above range, silicon-based materials have good electronic contact, which is beneficial to improving the lithium-ion transport performance of the negative electrode and enhancing the cycle stability and kinetic performance of solid-state battery cells.

[0132] Solid-state battery cells require pressing processes during fabrication, such as hot pressing, cold isostatic pressing, or warm isostatic pressing. The porosity range of the negative electrode active material layer mentioned above refers to the porosity of the negative electrode active material layer after pressing, and the porosity of the negative electrode active material layer mentioned above refers to the porosity of the negative electrode active material layer after the solid-state battery cell has been discharged. The porosity test results of the negative electrode active material layer will change after the solid-state battery cell has been fully charged.

[0133] The porosity of the negative electrode active material layer can be tested as follows: After fully discharging a fresh solid-state battery cell, the negative electrode layer is removed and prepared as a single-sided coated negative electrode layer (if it is a double-sided coated negative electrode layer, the negative electrode active material layer on one side can be wiped off first). This is then cut into small circular samples of a certain area, and the apparent volume V1 of the sample is calculated. Referring to GB / T24586-2009, using inert nitrogen gas as the medium, the true volume V2 of the sample is measured using a gas displacement method and a true density meter. The porosity of the negative electrode active material layer = (V1-V2) / V1×100%. Multiple samples (e.g., 30 samples) with good appearance and no powder shedding at the edges can be tested, and the average value of the results is taken, which can improve the accuracy of the test results. The testing instrument can be a Micromeritics AccuPyc II 1340 true density meter.

[0134] In some embodiments, the thickness of the negative electrode active material layer can be 1μm-40μm, for example, it can be 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 22μm, 24μm, 26μm, 28μm, 30μm, 32μm, 34μm, 36μm, 38μm, 40μm, or any range of the above values.

[0135] Optionally, the thickness of the negative electrode active material layer can be 1μm-30μm, 1μm-24μm, 1μm-18μm, 1μm-12μm, 1μm-6μm, 2μm-30μm, 2μm-24μm, 2μm-18μm, 2μm-12μm, or 2μm-6μm.

[0136] In some embodiments, the negative electrode layer further includes a metal layer located between the negative electrode current collector and the negative electrode active material layer, the metal layer comprising a metal element capable of forming an alloy or solid solution with lithium.

[0137] The metal layer includes metallic elements that can form alloys or solid solutions with lithium, thereby reducing the overpotential for lithium nucleation, improving the uniformity of lithium deposition, and enhancing the cycle performance of solid-state battery cells.

[0138] Optionally, the metal element in the metal layer includes one or more of Au, Ag, Mg, Zn, Sn, Bi, In, and Al.

[0139] Optionally, the thickness of the metal layer is 1nm-50nm, for example, it can be 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 22nm, 24nm, 26nm, 28nm, 30nm, 32nm, 34nm, 36nm, 38nm, 40nm, 42nm, 44nm, 46nm, 48nm, 50nm, or any combination of the above values.

[0140] In some embodiments, the negative electrode layer further includes a lithium-based metal layer located between the negative electrode current collector and the negative electrode active material layer.

[0141] During operation, lithium undergoes an alloying lithium intercalation reaction with silicon-based materials in a solid-state battery cell. However, during discharge, some lithium is difficult to extract from the silicon-based materials. Furthermore, the volume expansion of the silicon-based materials during cycling also causes irreversible lithium loss. The solid-state battery cell disclosed in this invention incorporates a lithium-based metal layer between the negative electrode current collector and the negative electrode active material layer before charging. This layer can compensate for the irreversible lithium loss from the negative electrode active material layer, thereby further improving the initial coulombic efficiency and capacity retention of the solid-state battery cell.

[0142] Optionally, the lithium-based metal layer may include lithium or a lithium alloy, and optionally include lithium.

[0143] Optionally, the lithium-based metal layer can continuously cover the surface of the negative electrode current collector.

[0144] Optionally, the lithium-based metal layer is discontinuous in the length and / or width direction of the negative electrode current collector, that is, the surface of the negative electrode current collector has intermittent regions where no lithium-based metal layer is disposed.

[0145] Optionally, the thickness of the lithium-based metal layer can be 0.5μm-50μm, for example, it can be 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 22μm, 24μm, 26μm, 28μm, 30μm, 32μm, 34μm, 36μm, 38μm, 40μm, 42μm, 44μm, 46μm, 48μm, 50μm, or any range of the above values.

[0146] Alternatively, the thickness of the lithium-based metal layer can be 1μm-30μm, 1μm-20μm, 1μm-15μm, 1μm-10μm, 3μm-30μm, 3μm-20μm, 3μm-15μm, 3μm-10μm, 5μm-30μm, 5μm-20μm, 5μm-15μm, or 5μm-10μm.

[0147] Optionally, the lithium-based metal layer can be a lithium-based metal layer with a passivation layer on its surface. Optionally, the passivation layer can include one or more of Li₂O, Li₂O₂, Li₂CO₃, and LiOH. Optionally, the thickness of the passivation layer can be greater than 0 and less than or equal to 30 nm, for example, it can be 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, 30 nm, or any range of the above values. More preferably, the thickness of the passivation layer can be 2 nm-30 nm, 4 nm-30 nm, 6 nm-30 nm, 8 nm-30 nm, or 10 nm-30 nm.

[0148] In some embodiments, the negative electrode layer further includes a metal layer and a lithium-based metal layer located between the negative electrode current collector and the negative electrode active material layer. The metal layer includes a metal element capable of forming an alloy or solid solution with lithium, and the lithium-based metal layer is configured to be close to the negative electrode current collector, while the other metal layer is configured to be far away from the negative electrode current collector.

[0149] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. The metal foil may be a pure metal, an alloy, or a surface-treated metal, such as, but not limited to, stainless steel foil, copper foil, and nickel foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. As an example, the metal layer may include, but is not limited to, one or more of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymer substrate may include, but is not limited to, one or more of polypropylene, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene, and polyethylene.

[0150] The negative electrode layer can be prepared by a dry process or a wet process. In some embodiments, the negative electrode layer can be formed by coating a negative electrode slurry, including a silicon-based material and a negative electrode conductive agent, onto a negative electrode current collector, followed by drying and cold pressing. In other embodiments, the negative electrode layer can be obtained by combining a dry-process negative electrode active material layer, including a silicon-based material and a negative electrode conductive agent, with a negative electrode current collector.

[0151] [Positive electrode layer]

[0152] The positive electrode layer can be prepared by either a dry process or a wet process.

[0153] In some embodiments, the positive electrode layer includes a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector, wherein the positive electrode active material layer includes a solid electrolyte material and a positive electrode active material.

[0154] In some embodiments, the positive current collector may be a metal foil or a composite current collector. The metal foil may be a pure metal, an alloy, or a surface-treated metal, such as, but not limited to, stainless steel foil, carbon-coated aluminum foil, or aluminum foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. As an example, the metal layer may include, but is not limited to, one or more of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymer substrate may include, but is not limited to, one or more of polypropylene, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene.

[0155] In some embodiments, the positive electrode layer may not require an additional positive electrode current collector; for example, the stainless steel sheet of a molded battery can be used directly as the positive electrode current collector.

[0156] In some embodiments, the positive electrode active material may include one or more of lithium transition metal oxides and their modified forms, lithium phosphates and their modified forms, lithium titanate, lithium niobate, sulfur, selenium, and tellurium.

[0157] Optionally, examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxides, lithium nickel oxides, lithium manganese oxides, lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, lithium nickel cobalt manganese oxides, lithium nickel cobalt aluminum oxides, and lithium-rich manganese-based materials.

[0158] Optionally, examples of lithium phosphates may include, but are not limited to, one or more of lithium iron phosphate, lithium iron phosphate and carbon composites, lithium manganese phosphate, lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.

[0159] In some embodiments, to further improve the energy density of a solid-state battery cell, the positive electrode active material may include materials of the general formula Li. a Ni b Co c M d O e A fOne or more of lithium transition metal oxides and their modified materials. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M may include one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A may include one or more of N, F, S and Cl.

[0160] As an example, the positive electrode active material may include, but is not limited to, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (abbreviated as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (abbreviated as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (abbreviated as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (abbreviated as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (abbreviated as NCM811), LiNi 0.96 Co 0.02 Mn 0.02 O2 (abbreviated as Ni96), LiNi 0.80 Co 0.15 Al 0.05 One or more of O2, LiFePO4, LiMnPO4 and their respective modified materials.

[0161] The modified materials for the above-mentioned positive electrode active materials can be the positive electrode active materials through doping modification and / or surface coating modification.

[0162] During the charging and discharging process, solid-state battery cells undergo Li insertion / extraction and consumption, resulting in varying Li molar content at different discharge states. In this disclosure, the Li molar content listed for positive electrode active materials represents the initial state of the material, i.e., the state before material addition. As the positive electrode active material is applied to a solid-state battery cell, the Li molar content changes after charge-discharge cycles. Similarly, the O molar content listed for positive electrode active materials in this disclosure is only a theoretical value; lattice oxygen release causes changes in the O molar content, leading to fluctuations in the actual O molar content.

[0163] In some embodiments, the solid electrolyte material in the positive electrode layer may include one or more of a sulfide solid electrolyte material, a halide solid electrolyte material, an oxide solid electrolyte material, and a polymer solid electrolyte material.

[0164] In some embodiments, the sulfide solid electrolyte material may include, but is not limited to, one or more of argyrodite-type, LGPS-type, and lithium sulfide-phosphorus pentasulfide composite-based sulfide solid electrolyte materials.

[0165] Alternatively, the argyrodite-type sulfide solid electrolyte material may include a material with the chemical formula Li 6±s P 1-j A j S 5±s- t B t X 1±s where 0≤j<1, 0≤t<1, 0≤s<1, A includes one or more elements selected from Ge, Si, Sn and Sb, B includes one or more elements selected from O, Se and Te, and X includes one or more elements selected from Cl, Br, I and F.

[0166] Alternatively, the LGPS-type sulfide solid electrolyte material may include a material with the chemical formula Li 10±δ5 Ge 1-g G g P 2-q Q q S 12- w W w where 0≤δ5<1, 0≤g≤1, 0≤q≤2, 0≤w<1, G includes one or two elements selected from Si and Sn, Q includes Sb, and W includes one or more elements selected from O, Se, Te, Cl, Br, I and F.

[0167] Alternatively, the lithium sulfide-phosphorus pentasulfide composite-based sulfide solid electrolyte material may include a material with the chemical formula (100-u-v)Li2S·uP2S5·vM m N n where 0<u<100, 0≤v<100, 0≤u+v<100, 0≤m<4, 0≤n<6, M includes one or more elements selected from Li, B, Ge, Si, Sn and Sb, and N includes one or more elements selected from S, Se, Te, O, Cl, Br, I and F.

[0168] As an example, the sulfide solid electrolyte material may include, but is not limited to, Li6PS5Cl, Li6PS5Br, Li 10 GeP2S 12 , Li3PS4, Li7P3S 11One or more of them.

[0169] In some embodiments, the halide solid electrolyte material may include, but is not limited to, one or more of Li3YCl6, Li3YBr6, Li3ErCl6, Li3InCl6, and Li3InBr6.

[0170] In some embodiments, the oxide solid electrolyte material may include one or more of the following: NASICON type solid electrolyte, LISICON type solid electrolyte, perovskite type solid electrolyte, and garnet type solid electrolyte.

[0171] As an example, oxide solid electrolyte materials may include, but are not limited to, Li5La3Ti2O 12 Li7La3Zr2O 12 Li4Ti5O 12 Li 14 Zn(GeO4)4, LiTi2(PO4)3, Li 1+x Al x Ti 2-x (PO4)3, Li 1+y Al y Ge 2-y One or more of (PO4)3, 0 < x < 2, 0 < y < 2.

[0172] In some embodiments, the polymer solid electrolyte material may be formed by complexing a polymer matrix material with a lithium salt. Optionally, the polymer matrix material may be one or more of, but not limited to, polyethylene oxide (PEO) and its derivatives, polypropylene oxide (PPO) and its derivatives, polycarbonate (PPC), polyacrylonitrile (PAN), polysiloxane (PDMS), polyvinylidene fluoride (PVDF), and polymethyl methacrylate (PMMA). Optionally, the lithium salt may be one or more of, but not limited to, LiClO4, LiAsF4, LiPF6, LiBF4, LiTFSI, and LiFSI.

[0173] Optionally, the polymer solid electrolyte material may also include an inert filler, which can reduce the crystallinity of the polymer and improve its mechanical properties. Optionally, the inert filler may be one or more of TiO2, Al2O3, ZrO2, and SiO2.

[0174] In some embodiments, the positive electrode active material layer may further include a positive electrode conductive agent.

[0175] Optionally, the positive electrode conductive agent may be one or more of the following, including but not limited to superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes (CNTs), graphene, carbon nanofibers, and vapor-grown carbon fibers (VGCF).

[0176] In some embodiments, the positive electrode active material layer may or may not include a positive electrode binder, and can be adjusted according to the positive electrode composition and the preparation process of the solid-state battery cell.

[0177] Optionally, the positive electrode binder may include, but is not limited to, one or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, methyl vinyl silicone rubber, nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), thermoplastic styrene-butadiene rubber (SBS), isoprene rubber, cis-butadiene rubber (BR), ethyl cellulose, fluororubber, and acrylate rubber.

[0178] In some embodiments, the positive electrode capacity per unit area can be 2.5 mAh / cm². 2 -6mAh / cm 2 The positive electrode capacity per unit area is the capacity that the positive electrode active material layer on one side of the positive electrode current collector can provide per unit area.

[0179] [Electrolyte layer]

[0180] The electrolyte layer can be prepared by a dry process or a wet process.

[0181] In some embodiments, the electrolyte layer comprises a solid electrolyte material.

[0182] Optionally, the solid electrolyte material may include one or more of the following: sulfide solid electrolyte material, halide solid electrolyte material, oxide solid electrolyte material, and polymer solid electrolyte material.

[0183] In some embodiments, the sulfide solid electrolyte material may include, but is not limited to, one or more of the following: silver-germanium sulfide type, LGPS type, lithium sulfide-phosphorus pentasulfide complex type sulfide solid electrolyte materials.

[0184] Optionally, the sulfide solid electrolyte material of the silver-germanium sulfide type may include Li 6±s P 1-j A j S 5±s- t B t X 1±s The material has the following properties: 0≤j<1, 0≤t<1, 0≤s<1, A includes one or more elements from Ge, Si, Sn and Sb, B includes one or more elements from O, Se and Te, and X includes one or more elements from Cl, Br, I and F.

[0185] Optionally, the LGPS-type sulfide solid-state electrolyte material may include a chemical formula of Li 10±δ5 Ge 1-g G g P 2-q Q q S 12- w W w wherein 0≤δ5<1, 0≤g≤1, 0≤q≤2, 0≤w<1, G includes one or two elements of Si and Sn, and Q includes Sb, W includes one or more elements of O, Se, Te, Cl, Br, I and F.

[0186] Optionally, the sulfide solid-state electrolyte material of lithium sulfide-phosphorus pentasulfide complex may include a chemical formula of (100-u-v)Li2S·uP2S5·vM m N n wherein 0<u<100, 0≤v<100, 0≤u+v<100, 0≤m<4, 0≤n<6, M includes one or more elements of Li, B, Ge, Si, Sn and Sb, and N includes one or more elements of S, Se, Te, O, Cl, Br, I and F.

[0187] As an example, the sulfide solid-state electrolyte material may include but is not limited to one or more of Li6PS5Cl, Li6PS5Br, Li 10 GeP2S 12 , Li3PS4, Li7P3S 11 .

[0188] In some embodiments, the halide solid-state electrolyte material may include but is not limited to one or more of Li3YCl6, Li3YBr6, Li3ErCl6, Li3InCl6, and Li3InBr6.

[0189] In some embodiments, the oxide solid-state electrolyte material may include one or more of a NASICON-type solid-state electrolyte, a LISICON-type solid-state electrolyte, a perovskite-type solid-state electrolyte, and a garnet-type solid-state electrolyte.

[0190] As an example, the oxide solid-state electrolyte material may include but is not limited to Li5La3Ti2O 12 , Li7La3Zr2O 12 , Li4Ti5O 12 , Li 14 Zn(GeO4)4, LiTi2(PO4)3, Li 1+x Al x Ti 2-x(PO4)3, Li 1+y Al y Ge 2-y One or more of (PO4)3, 0 < x < 2, 0 < y < 2.

[0191] In some embodiments, the polymer solid electrolyte material may be formed by complexing a polymer matrix material with a lithium salt. Optionally, the polymer matrix material may be one or more of, but not limited to, polyethylene oxide (PEO) and its derivatives, polypropylene oxide (PPO) and its derivatives, polycarbonate (PPC), polyacrylonitrile (PAN), polysiloxane (PDMS), polyvinylidene fluoride (PVDF), and polymethyl methacrylate (PMMA). Optionally, the lithium salt may be one or more of, but not limited to, LiClO4, LiAsF4, LiPF6, LiBF4, LiTFSI, and LiFSI.

[0192] Optionally, the polymer solid electrolyte material may also include an inert filler, which can reduce the crystallinity of the polymer and improve its mechanical properties. Optionally, the inert filler may be one or more of TiO2, Al2O3, ZrO2, and SiO2.

[0193] In some embodiments, the electrolyte layer may or may not include a binder, depending on the manufacturing process of the solid-state battery cell. Optionally, the binder may include, but is not limited to, one or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, methyl vinyl silicone rubber, nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), thermoplastic styrene-butadiene rubber (SBS), isoprene rubber, butadiene rubber (BR), ethyl cellulose, fluororubber, and acrylate rubber.

[0194] In some embodiments, the solid-state battery cell may further include an outer packaging for accommodating the electrode assembly formed by assembling the negative electrode layer, electrolyte layer, and positive electrode layer. The outer packaging may be a rigid shell, such as a hard plastic shell, aluminum shell, or steel shell. The outer packaging may also be a flexible package, such as a pouch. The material of the flexible package may be plastic, such as one or more of aluminum-plastic film, polypropylene, polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0195] [Preparation Method]

[0196] The methods for preparing solid-state battery cells are well known. For example, the assembly methods of solid-state battery cells include, but are not limited to, coin cells, molded cells, hard-case cells, and pouch cells.

[0197] In some embodiments, the method for preparing a solid-state battery cell includes the following steps: providing a negative electrode layer, an electrolyte layer, and a positive electrode layer; assembling the negative electrode layer, electrolyte layer, and positive electrode layer; and pressing them to obtain a solid-state battery cell. The electrolyte layer is located between the negative electrode layer and the positive electrode layer. The negative electrode layer includes a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector. The negative electrode active material layer includes a silicon-based material and a negative electrode conductive agent. The average particle size of the silicon-based material is 15nm-200nm. The NP ratio of the solid-state battery cell is greater than 0 and less than 1. The NP ratio is the ratio of the negative electrode unit area capacity to the positive electrode unit area capacity.

[0198] Alternatively, the pressing process can be flat hot pressing, cold isostatic pressing, or warm isostatic pressing.

[0199] Example

[0200] The following embodiments describe the disclosure of this disclosure in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of this disclosure. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0201] Example 1

[0202] Preparation of negative electrode layer

[0203] A negative electrode slurry was prepared by uniformly dispersing pure silicon (the active material), polyvinylidene fluoride (the binder), and carbon nanotubes (the conductive agent) in deionized water at a solid mass ratio of 97:2:1. The slurry was then uniformly coated onto a stainless steel negative electrode current collector, baked in an oven to remove the solvent, and finally cut to the appropriate size and welded with tabs to obtain the negative electrode layer. The negative electrode capacity per unit area was 2.7 mAh / cm². 2 The average particle size of pure silicon in the negative electrode active material layer is 30 nm.

[0204] Preparation of positive electrode layer

[0205] LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1O2, solid electrolyte material Li6PS5Cl, positive electrode conductive agent vapor-grown carbon fiber VGCF, and positive electrode binder polytetrafluoroethylene (PTFE) are mixed uniformly at a solid mass ratio of 70:25.5:2.5:2. The mixture is heated on an 80°C heating platform and repeatedly rolled to form a dry-process positive electrode active material layer. This layer is then laminated with aluminum foil as a positive electrode current collector using a hot roller, cut to the appropriate size, and welded with tabs to obtain the positive electrode layer. The positive electrode's unit area capacity is 3 mAh / cm². 2 .

[0206] Preparation of electrolyte layer

[0207] The solid electrolyte material Li6PS5Cl and the binder polytetrafluoroethylene (PTFE) were mixed evenly at a solid mass ratio of 98:2, heated on a heating table at 80°C, and rolled back and forth to form a dry electrolyte layer.

[0208] Preparation of solid-state battery cells

[0209] The prepared positive electrode layer, electrolyte layer, and negative electrode layer were assembled in an alternating stacked manner and hot-pressed. Then, they were encapsulated under negative pressure with an aluminum-plastic film to obtain a soft-pack solid-state battery cell. The NP ratio of the solid-state battery cell was 0.9. After hot-pressing, the porosity of the negative electrode active material layer was 15%.

[0210] Example 2

[0211] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 1.

[0212] The parameters of the negative electrode active material layer were adjusted to achieve a negative electrode capacity of 2.1 mAh / cm². 2 The NP ratio of a solid-state battery cell is 0.7.

[0213] Example 3

[0214] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 1.

[0215] The parameters of the negative electrode active material layer were adjusted to achieve a negative electrode capacity of 1.5 mAh / cm². 2 The NP ratio of a solid-state battery cell is 0.5.

[0216] Example 4

[0217] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 1.

[0218] The parameters of the negative electrode active material layer were adjusted to achieve a negative electrode capacity of 0.9 mAh / cm². 2 The NP ratio of a solid-state battery cell is 0.3.

[0219] Example 5

[0220] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 1.

[0221] The parameters of the negative electrode active material layer were adjusted to achieve a negative electrode capacity of 0.3 mAh / cm². 2 The NP ratio of a solid-state battery cell is 0.1.

[0222] Example 6

[0223] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 1.

[0224] The parameters of the negative electrode active material layer were adjusted to achieve a negative electrode capacity of 0.15 mAh / cm². 2 The NP ratio of a solid-state battery cell is 0.05.

[0225] Comparative Example 1

[0226] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 1.

[0227] The parameters of the negative electrode active material layer were adjusted to achieve a negative electrode capacity of 4.5 mAh / cm². 2 The NP ratio of a solid-state battery cell is 1.5.

[0228] Comparative Example 2

[0229] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 1.

[0230] The negative electrode active material, pure silicon, and the negative electrode binder, polyvinylidene fluoride, were uniformly dispersed in deionized water at a solid-to-mass ratio of 97:3 to obtain a negative electrode slurry. This slurry was then uniformly coated onto a stainless steel negative electrode current collector, baked in an oven to remove the solvent, and finally cut to the appropriate size and welded with tabs to obtain the negative electrode layer. The parameters of the negative electrode active material layer were adjusted to achieve a negative electrode capacity of 3 mAh / cm². 2 The NP ratio of the solid-state battery cell is 1. The average particle size of pure silicon in the negative electrode active material layer is 100 nm.

[0231] Comparative Example 3

[0232] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 1.

[0233] Preparation of negative electrode layer

[0234] The negative electrode active material, pure silicon, and the negative electrode binder, polyvinylidene fluoride, were uniformly dispersed in deionized water at a solid-to-mass ratio of 97:3 to obtain a negative electrode slurry. This slurry was then uniformly coated onto a stainless steel negative electrode current collector, baked in an oven to remove the solvent, and finally cut to the appropriate size and welded with tabs to obtain the negative electrode layer. The parameters of the negative electrode active material layer were adjusted to achieve a negative electrode capacity of 2.1 mAh / cm². 2 The NP ratio of the solid-state battery cell is 0.7. The average particle size of pure silicon in the negative electrode active material layer is 100 nm.

[0235] Performance testing

[0236] (1) First coulombic efficiency test of solid-state battery cell

[0237] At 25°C, solid-state battery cells were charged to 4.3V (vs. Li) at a current density of 0.1C. + / Li), let stand for 10 minutes, then discharge at a current density of 0.1C to 2V (vs. Li). + / Li), to obtain the specific capacity of the first charge and the specific capacity of the first discharge.

[0238] The initial coulombic efficiency (%) of a solid-state battery cell = first discharge specific capacity / first charge specific capacity × 100%.

[0239] (2) Rate performance test of solid-state battery cells

[0240] At 25°C, the solid-state battery cell was first charged to 4.3V (vs. Li) at a current density of 0.1C. + / Li), let stand for 10 minutes, then discharge at a current density of 0.1C to 2V (vs. Li). + / Li), and the capacity obtained by 3 cycles of charge and discharge is recorded as the discharge specific capacity at a rate of 0.1C;

[0241] The solid-state battery cells were then charged to 4.3V (vs. Li) at a current density of 0.33C. + / Li), let stand for 10 minutes, then discharge to 2V at a current density of 0.33C (vs. Li). + / Li), the obtained capacity is recorded as the discharge specific capacity at a rate of 0.33C;

[0242] The solid-state battery cells are then charged to 4.3V (vs. Li) at a current density of 0.5C. + / Li), let stand for 10 minutes, then discharge at a current density of 0.5C to 2V (vs. Li). + / Li), the obtained capacity is recorded as the discharge specific capacity at a rate of 0.5C;

[0243] The solid-state battery cells are then charged to 4.3V (vs. Li) at a current density of 1C. + / Li), let stand for 10 minutes, then discharge at a current density of 1C to 2V (vs. Li). + The capacity obtained is denoted as the discharge specific capacity at a 1C rate ( / Li).

[0244] (3) Cyclic performance test of solid-state battery cells

[0245] At 25°C, the solid-state battery cell was first charged to 4.3V (vs. Li) at a current density of 0.1C. + / Li), let stand for 10 minutes, then discharge at a current density of 0.1C to 2V (vs. Li). + / Li), cycle charge and discharge 3 times, the discharge capacity at this time is recorded as C1. Cycle charge and discharge a solid-state battery cell 50 times at a current density of 0.33C, the discharge capacity at this time is recorded as C2.

[0246] The capacity retention rate of a solid-state battery cell after 50 cycles at a current density of 0.33C is calculated as C2 / C1 × 100%.

[0247] During the above test, an external pressure of 5 MPa was applied to the solid-state battery cell.

[0248] Table 1

[0249]

[0250] The test results above show that by making the NP ratio of the solid-state battery cell greater than 0 and less than 1, making the negative electrode active material layer include silicon-based materials and negative electrode conductive agents, and making the average particle size of the silicon-based materials 15nm-200nm, the solid-state battery cell has high initial coulombic efficiency, good cycle stability and good rate performance under low external pressure.

[0251] Example 1-1

[0252] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 5.

[0253] The average particle size of pure silicon in the negative electrode active material layer is 50 nm.

[0254] Examples 1-2

[0255] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 5.

[0256] The average particle size of pure silicon in the negative electrode active material layer is 75 nm.

[0257] Examples 1-3

[0258] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 5.

[0259] The average particle size of pure silicon in the negative electrode active material layer is 85 nm.

[0260] Examples 1-4

[0261] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 5.

[0262] The average particle size of pure silicon in the negative electrode active material layer is 100 nm.

[0263] Examples 1-5

[0264] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 5.

[0265] The average particle size of pure silicon in the negative electrode active material layer is 150 nm.

[0266] Examples 1-6

[0267] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 5.

[0268] The average particle size of pure silicon in the negative electrode active material layer is 200 nm.

[0269] Table 2

[0270]

[0271] The test results above show that further adjusting the average particle size of silicon-based materials is beneficial to improving the first coulombic efficiency, cycle performance, and rate performance of solid-state battery cells.

[0272] Example 2-1

[0273] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 5.

[0274] A negative electrode slurry was prepared by uniformly dispersing pure silicon (negative electrode active material), polyvinylidene fluoride (negative electrode binder), and vapor-grown carbon fiber (VGCF) (negative electrode conductive agent) in deionized water at a solid mass ratio of 97:2:1. The negative electrode slurry was then uniformly coated onto a stainless steel negative electrode current collector, baked in an oven to remove the solvent, and finally cut to the appropriate size and welded with tabs to obtain the negative electrode layer. The negative electrode capacity per unit area was 0.3 mAh / cm². 2 The volumetric particle size distribution (Dv50) of pure silicon is 30 nm.

[0275] Example 2-2

[0276] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 5.

[0277] A negative electrode slurry was prepared by uniformly dispersing pure silicon (the active material), polyvinylidene fluoride (the binder), and carbon black (the conductive agent) in deionized water at a solid mass ratio of 97:2:1. The slurry was then uniformly coated onto a stainless steel negative electrode current collector, baked in an oven to remove the solvent, and finally cut to the appropriate size and welded with tabs to obtain the negative electrode layer. The negative electrode capacity per unit area was 0.3 mAh / cm². 2 The average particle size of pure silicon in the negative electrode active material layer is 30 nm.

[0278] Example 2-3

[0279] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 5.

[0280] A negative electrode slurry was prepared by uniformly dispersing pure silicon (the active material), polyvinylidene fluoride (the binder), and graphene (the conductive agent) in deionized water at a solid mass ratio of 97:2:1. The slurry was then uniformly coated onto a stainless steel negative electrode current collector, baked in an oven to remove the solvent, and finally cut to the appropriate size and welded with tabs to obtain the negative electrode layer. The negative electrode capacity per unit area was 0.3 mAh / cm². 2 The average particle size of pure silicon in the negative electrode active material layer is 30 nm.

[0281] Table 3

[0282]

[0283] The test results above show that including linear conductive agents in the negative electrode conductive agent is beneficial to improving the initial coulombic efficiency, cycle performance, and rate performance of solid-state battery cells.

[0284] Example 3-1

[0285] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 5.

[0286] The heat treatment parameters were adjusted so that the porosity of the negative electrode active material layer after hot pressing was 10%.

[0287] Example 3-2

[0288] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 5.

[0289] The heat treatment parameters were adjusted so that the porosity of the negative electrode active material layer after hot pressing was 20%.

[0290] Example 3-3

[0291] Except for the following differences, the preparation method of the solid-state battery cell is the same as that in Example 5.

[0292] The heat treatment parameters were adjusted so that the porosity of the negative electrode active material layer after hot pressing was 25%.

[0293] Table 4

[0294]

[0295] The test results above show that further adjusting the porosity of the negative electrode active material layer is beneficial to improving the first coulombic efficiency, cycle performance and rate performance of solid-state battery cells.

[0296] It should be noted that this disclosure is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this disclosure are included within the technical scope of this disclosure. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, are also included within the scope of this disclosure without departing from the spirit of this disclosure.

Claims

1. A solid-state battery cell, comprising a negative electrode layer, an electrolyte layer, and a positive electrode layer, wherein the electrolyte layer is located between the negative electrode layer and the positive electrode layer, characterized in that, The negative electrode layer includes a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector. The negative electrode active material layer includes a silicon-based material and a negative electrode conductive agent. The average particle size of the silicon-based material is 15nm-200nm. The NP ratio of the solid-state battery cell is greater than 0 and less than 1. The NP ratio is the ratio of the negative electrode unit area capacity to the positive electrode unit area capacity.

2. The solid-state battery cell according to claim 1, characterized in that, The average particle size of the silicon-based material is 30nm-85nm.

3. The solid-state battery cell according to claim 1, characterized in that, The volumetric particle size Dv50 of the silicon-based material is 15nm-200nm.

4. The solid-state battery cell according to any one of claims 1-3, characterized in that, The NP ratio of the solid-state battery cell is 0.05-0.

3.

5. The solid-state battery cell according to any one of claims 1-4, characterized in that, The solid-state battery cell operates under an external pressure of less than 10 MPa.

6. The solid-state battery cell according to any one of claims 1-5, characterized in that, The silicon-based material includes pure silicon or silicon-containing materials.

7. The solid-state battery cell according to claim 6, characterized in that, The silicon-containing material includes metal-doped silicon, wherein the mass fraction of Si element in the metal-doped silicon is greater than or equal to 75% and less than 100%.

8. The solid-state battery cell according to claim 7, characterized in that, The atomic radius r of the doped metal element in the metal-doped silicon is the same as the atomic radius r of the Si element. si Satisfy (rr) si ) / r×100% is between 0 and 25%.

9. The solid-state battery cell according to claim 8, characterized in that, The doping metal element in the metal-doped silicon includes one or more of Ge, Sn, Fe, Ni, Al, and Cu.

10. The solid-state battery cell according to any one of claims 1-9, characterized in that, With the total mass of the negative electrode active material layer being 100%, the mass fraction of Si element in the negative electrode active material layer is greater than 50% and less than 100%.

11. The solid-state battery cell according to claim 10, characterized in that, With the total mass of the negative electrode active material layer as 100%, the mass fraction of Si element in the negative electrode active material layer is 80%-98%.

12. The solid-state battery cell according to any one of claims 1-11, characterized in that, The negative electrode conductive agent includes a linear conductive agent.

13. The solid-state battery cell according to claim 12, characterized in that, The linear conductive agent includes one or more of carbon nanotubes, carbon nanofibers, and vapor-grown carbon fibers; and / or The linear conductive agent accounts for 0.5%-2% of the mass of the negative electrode active material layer.

14. The solid-state battery cell according to claim 12 or 13, characterized in that, The negative electrode conductive agent also includes dot-shaped conductive agents and / or surface-shaped conductive agents.

15. The solid-state battery cell according to any one of claims 1-14, characterized in that, The negative electrode active material layer also includes a solid electrolyte material, which includes one or more of the following: sulfide solid electrolyte material, halide solid electrolyte material, oxide solid electrolyte material, and polymer solid electrolyte material.

16. The solid-state battery cell according to any one of claims 1-15, characterized in that, The porosity of the negative electrode active material layer is 10%-20%; and / or, The thickness of the negative electrode active material layer is 1μm-40μm.

17. The solid-state battery cell according to claim 16, characterized in that, The thickness of the negative electrode active material layer is 2μm-6μm.

18. The solid-state battery cell according to any one of claims 1-17, characterized in that, The negative electrode layer further includes a metal layer located between the negative electrode current collector and the negative electrode active material layer, the metal layer comprising a metal element capable of forming an alloy or solid solution with lithium.

19. The solid-state battery cell according to claim 18, characterized in that, The metallic element in the metal layer includes one or more of Au, Ag, Mg, Zn, Sn, Bi, In, and Al; and / or, The thickness of the metal layer is 1nm-50nm.

20. The solid-state battery cell according to any one of claims 1-19, characterized in that, The negative electrode layer also includes a lithium-based metal layer located between the negative electrode current collector and the negative electrode active material layer. The lithium-based metal layer comprises lithium or a lithium alloy; and / or, The thickness of the lithium-based metal layer is 0.5μm-50μm.

21. The solid-state battery cell according to any one of claims 1-20, characterized in that, The positive electrode layer includes a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector. The positive electrode active material layer includes a solid electrolyte material and a positive electrode active material. The positive electrode active material includes one or more of lithium transition metal oxides and their modified materials, lithium phosphates and their modified materials, lithium titanate, lithium niobate, sulfur, selenium, and tellurium. The solid electrolyte material includes one or more of sulfide solid electrolyte materials, halide solid electrolyte materials, oxide solid electrolyte materials, and polymer solid electrolyte materials; and / or, The electrolyte layer includes one or more of the following: sulfide solid electrolyte material, halide solid electrolyte material, oxide solid electrolyte material, and polymer solid electrolyte material.

22. The solid-state battery cell according to claim 21, characterized in that, The positive electrode has a capacity per unit area of ​​2.5 mAh / cm². 2 -6mAh / cm 2 .

23. A method for preparing a solid-state battery cell, comprising the following steps: providing a negative electrode layer, an electrolyte layer, and a positive electrode layer; assembling the negative electrode layer, the electrolyte layer, and the positive electrode layer; and pressing them to obtain a solid-state battery cell, wherein the electrolyte layer is located between the negative electrode layer and the positive electrode layer; the negative electrode layer includes a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector; the negative electrode active material layer includes a silicon-based material and a negative electrode conductive agent; the average particle size of the silicon-based material is 15nm-200nm; and the NP ratio of the solid-state battery cell is greater than 0 and less than 1, wherein the NP ratio is the ratio of the negative electrode unit area capacity to the positive electrode unit area capacity.

24. A battery device, characterized in that, Includes solid-state battery cells as described in any one of claims 1-22 or solid-state battery cells prepared by the preparation method described in claim 23.

25. An electrical appliance, characterized in that, Includes the solid-state battery cell according to any one of claims 1-22 or the battery device according to claim 24.